PERANAN PEMBENTUKAN KARAKTER DAN MORALITAS KEAGAMAAN UNTUK PEMBERANTASAN KORUPSI - Dalmeri Dalmeri (Ri'ayah: Jurnal Sosial dan Keagamaan, 2016)
Reality of paradoxical in Indonesian existence shows that the corruption achievements is improve as wll as the diversity of the people. It shows that the pattern of religious people still in the theoretical-formalistic stage. It seems the religius leader attempts to tease the religion doctrin to destroy the social structure of community life. Corruption has become a cultural and traditions that haunting destruction the character of Indonesian nation because people who have distort the authority given by the people of Indonesia. That they do corruption can the resulted crisis economical, crisis politic and also poornes, jobles and criminalty, starvation, hardness with others. Majority the people Indonesia regarded as people who are religious. This phenomenon can build character and religious morality to apply teachings of religion to eradicate corruption. This paper seeks to analyze the role and function of religion as a source of kindness and instructions in social life in order to building the character and morality of religion to eradicate corruption.